Which is the better polyp detection metric: adenomas per colonoscopy or adenoma detection rate? A simulation modeling study - MacKenzie, Todd; Xiao, Sikai; Hisey, William H; Robinson, Christina M; Butterly, Lynn; Anderson, Joseph C (Endoscopy International Open, 2024)
Background and study aims We compared the ability of adenoma detection rate (ADR) and adenoma per colonoscopy (APC) to assess endoscopist detection, using statistical principles and simulations.Patients and methods We simulated a population of endoscopists and patients to compare the ability of ADR versus APC for capturing true endoscopist ability (TEA). We compared these rates with and without adjustment for patient and exam factors using multivariable models, and adjustment for imprecision due to low volume using empirical Bayes (shrinkage). Power calculations were used to compare the ability of ADR and APC to distinguish higher from lower rates over two time periods for an endoscopist.Results APC and ADR had similar discriminatory ability for assessing TEA. This increased with higher volumes and after adjusting for risk factors and low volume using shrinkage. Higher APC and ADRs had higher power for comparing endoscopist detection over two time periods, but APC was superior to ADR. For example, there was 29% power to distinguish APCs (n = 200 colonoscopies) 0.10 from 0.15, similar to the power (28%) to distinguish corresponding ADRs: 10% and 14%. However, at same volume (n = 200), the power to distinguish higher APC rates (0.50 vs.0.75) was greater (89%) than the power (78%) for corresponding ADRs (39% vs.53%).Conclusions Adjusting for patient and exam factors and/or using shrinkage techniques for lower-volume endoscopists can increase the correlation between TEA for both ADR and APC. For higher detection rates, APC offers more power than ADR in distinguishing differences in detection ability.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; CRC screening; Statistics